Knowledge and Attitude Towards Bell’s Palsy Rehabilitation Among Physical Therapists in Saudi Arabia: A Cross-Sectional Study - Albishi AM; Al-Ageel HM; AlAbdulwahab SS (Dove Medical Press, 2024)
Alaa M Albishi, Hanan M Al-Ageel, Sami S AlAbdulwahab Department of Health Rehabilitation Sciences, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Alaa M Albishi; Hanan M Al-Ageel, King Saud University, P.O. Box 10219, Riyadh, 11433, Saudi Arabia, Email aalbeshi@ksu.edu.sa; hanan4pt@gmail.comBackground: Bell's Palsy (BP) is an acute lower motor nerve impairment of the facial nerve, causing sudden paralysis on one side of the face and significantly affecting the patient's quality of life. Physiotherapy is critical for rehabilitation after BP, aiding functional recovery. Various physical therapy interventions, such as dry needling, taping, and nerve mobilization, have proven effective in treating BP. However, different rehabilitation approaches and knowledge levels among therapists can result in varying treatment outcomes. Therefore, understanding rehabilitation specialists' knowledge and attitudes towards BP is essential for ensuring effective treatment. To date, no studies have examined the knowledge and attitudes of rehabilitation professionals in Saudi Arabia regarding BP.Objective: This study aims to evaluate the knowledge and attitudes of physical therapists in Saudi Arabia regarding the rehabilitation of BP.Methods: A cross-sectional observational study was conducted with 150 licensed physical therapists in Saudi Arabia, selected via convenience sampling. Participants completed an anonymous online survey covering demographics, knowledge of, and attitudes toward BP rehabilitation techniques. Descriptive and inferential statistics were used to analyze the data.Results: The participants had a mean age of 33.13 ± 6.85 years, with 68.7% being female. Most held Bachelor's degrees (65.3%) and worked in general hospitals (72.7%). The average knowledge score was 8.99 ± 1.95, indicating moderate knowledge levels. Attitudes towards BP rehabilitation were positive, particularly regarding early intervention, emotional support, and coordination exercises. Significant differences in knowledge and attitudes were observed based on gender, experience, and practice location.Conclusion: Physical therapists in Saudi Arabia demonstrate moderate knowledge and positive attitudes toward BP rehabilitation. Continued professional education and collaboration are recommended to improve clinical standards in treating BP.Keywords: Bell's palsy, facial palsy, mime therapy, physical therapist, rehabilitation, knowledge, Attitudes, Saudi Arabia